REPRESENTASI MASKOT INES DAN IMAN PADA SOSIALISASI INTERNET SEHAT DAN AMAN - Mustika, Rieka; Ariyani, Ika Deasy (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
Mascot used officially for media campaign by Kominfo team of Healthy Internet Dissemination is required to encourage public participation in the use of Healthy Internet. The purpose of this study is to know the meaning behind the formation of mascot Ines and Iman. This study uses a semiotic analysis of Ferdinand de Saussure. This research is qualitative descriptive, and data collection was done by the documentation and study of literature. The result shows that the mascot Ines plays role of the doctor who in charge of health problems which is associated with Healthy Internet, while the mascot Iman plays role of detective which is linked to the security or Safe Internet.